THE EFFECT OF ADDITIONAL AMOUNT OF CATFISHSURIMI (Pangasiushypophthalmus) WHICH IS DIFFERENT ON PROCESSING PROCESS OF PEMPEK TOWARDS CONSUMER ACCEPTANCE - Zuarli, Zuarli; Dahlia, Dahlia; Dewita, Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThe purpose of this research are to know the effect of additional amount ofcatfishsurimi which is different onProcessing process of pempek towardsconsumer acceptance, to know the best concentrate additional of catfish surimi toward pempek processed, and to know the pempek protein produced based on the proximate test. The experimental research method was the addition of catfishsurimi to pempek. The research design was completely randomized design (CRD) consisting of 4 treatment levels, namely without the addition of catfishsurimi (P0), the addition of 100 grams of catfish surimi (P1), 200 grams (P2), 300 grams (P3). Analysis parameters of organoleptic, moisture content, ash, fat, and protein. The results showed that the addition of different amounts of to catfish surimi processing of pempek had a significant effect on the 95% confidence level of pempek. The 300 gram catfish surimi (P3) produces the best value for pempek with not too white color, distinctive aroma of catfish surimi, compact texture and quite chewy, has a good taste; Pempeksurimi catfish has 50.78% water, 0.2.78% ash, 15.41% protein, and 0.68% fat.Keywords: catfish, surimi, pempek, consumer acceptance